Prawo Unii Europejskiej a wartości chrześcijańskie - Krukowski, Józef (Biuletyn Stowarzyszenia Kanonistów Polskich, 2012)
The Author explained the term of the law and the term of the values, especially Christian values. In the article, the Author distinguished two categories of the Christian values: 1) peculiar Christian values based on the theological grounds singling out religion and Christian ethic. The Church regulates the means of the achievement of these values with the assistance of the canon law; 2) universal ethical principles, which are basic human values, such as respect for the hierarchy of values, recognition that human being is in the first place in that hierarchy and recognition that the natural human dignity is a source of the fundamental rights and freedoms. The law of the European Union refers to the values. Politicians of the European Union have made the project of building the community called “European civil society”. Christians as the citizens of the European Union, should not be just passive observers while basic universal Christian values are disregarded. They should demand from politicians to respect the principle of the common good.